2013
DOI: 10.1007/s10973-013-3071-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of BaCe1−xYxO3−δ–BaWO4 composite protonic conductors

Abstract: Barium cerate doped by trivalent rare earth metal ions is a potentially huge component of materials for electrochemical industry due to its high protonic conductivity. However, the poor chemical stability especially in the presence of CO 2 , SO 2 or H 2 O, resulting in decreasing the mechanical durability of obtained materials, limits their possible applications. The new approach towards stable ceramic protonic conductors with high electrical conductivity is presented. Thermal stability of yttrium doped (10 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…One of their major applications is that tungsten oxides, metal tungstates, tungsten carbides or tungsten metal can be prepared from them, all of which are significant for various industries. Tungsten oxides can be used as catalysts [2][3][4][5], photocatalysts [6][7][8][9][10], gas sensors [11][12][13][14][15][16][17][18], chromogenic materials [19][20][21]; metal tungstates can be used among others as catalysts [22], pigments [23,24]; tungsten carbides are the hard components in cutting, drilling, tools [25][26][27] and they are also used as catalysts [28,29]; while tungsten metal is a key element in lighting industry [1,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…One of their major applications is that tungsten oxides, metal tungstates, tungsten carbides or tungsten metal can be prepared from them, all of which are significant for various industries. Tungsten oxides can be used as catalysts [2][3][4][5], photocatalysts [6][7][8][9][10], gas sensors [11][12][13][14][15][16][17][18], chromogenic materials [19][20][21]; metal tungstates can be used among others as catalysts [22], pigments [23,24]; tungsten carbides are the hard components in cutting, drilling, tools [25][26][27] and they are also used as catalysts [28,29]; while tungsten metal is a key element in lighting industry [1,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…High crystalline WO 3 was obtained for 20% Fe-doped WO 3 and this effect can also be observed on Fe-doped TiO 2 [31]. The main peak was shifted to lower lattice parameters due to the size of ionic radii of Fe 2+ (0.064 nm) [39], which was larger than W 6+ (0.060) [40]. The shifted peak also suggested that Fe 2+ had successfully replaced some of the W 6+ in bulk WO 3 lattice and thus, Fe-doped WO 3 was successfully synthesized.…”
Section: Xrd Analysismentioning
confidence: 75%
“…This study is essentially expected to contribute towards the ongoing efforts to obtain dense ceramic products from nanometric particles for SOFCs based on the application of proton conductors. [14] 1400 °C/5 h Conventional solid-state reaction route [46,47] 1200 °C/6 h Conventional solid-state reaction route [48] 1200 °C/12 h Conventional solid-state reaction route [49] 1150 °C/2 h Conventional solid-state reaction route [50] 1350 °C/6 h Conventional solid-state reaction route [15] 1150 °С/2 h Conventional solid-state reaction route [51] 1350 °C/10 h conventional solid-state reaction route [52] 1350 •C/10 h Conventional solid state reaction route [53] 1400 °C/10 h Conventional solid state reaction route [54] 950 °C/2 h Polymeric precursors route This work…”
Section: Discussionmentioning
confidence: 99%